Subtitling Language Diversity in Spanish Immigration Films - De Higes-Andino, Irene; Prats-Rodríguez, Ana; Martínez-Sierra, Juan; Chaume, Frederic (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
In Spain, the growing number of films depicting characters in multicultural settings bears testimony to the demographic changes experienced by Spanish society since the late 1980s. From a translational point of view, these films attract attention of researchers because of the presence of immigrant characters that use their mother tongue in addition to the language(s) of their host society. In this paper we present the results of the second stage of a research on the linguistic diversity in Spanish films starring immigrants. While the first stage dealt with the original audiovisual texts, we focus on their subtitled versions in two European languages. To do so, a descriptive and empirical methodology has been followed, the first step of which was the creation of a thorough corpus of six Spanish films and their corresponding eight target versions (in English and French). The descriptive and microtextual analysis of the immigrants’ dialogues found in our corpus allows us to define the translation strategies and techniques employed by subtitlers. Then, these techniques are classified in a continuum according to their degree of domestication and foreignisation. Finally, some conclusions are drawn regarding the ideology behind the cinematographic reflection of immigrants’ foreignness.